Shear behavior of web-embedded steel-concrete composite beam. Issue 5 (April 2023) - Yang, Yuanlong; Han, Jinjun; Zhao, Yi; Yu, Yingying; Chen, Yohchia F
To optimize conventional composite beam, this paper proposes a new steel-concrete composite beam without top flange, and discusses the shear behavior of this novel web-embedded steel-concrete composite beam (WSCB). Five patterns of embedded shear connectors are proposed, including the shapes of swallow tail, gear, modified gear, circular hole, and steel bar. A shear experiment on ten specimens with the shear span ratio λ = 1.5 were conducted, considering effects of the concrete slab width ( B ) and the shear connector pattern. The experiments showed two typical shear failure modes depending on the shear connector type. All five kinds of shear connectors guaranteed good integral action in the specimens. The concrete slab width B shows an obvious positive effect on the shear capacity and ductility. Furthermore, a FE model was established and verified by the experimental results to investigate the shear mechanism of WSCB. According to the experimental and numerical analysis results, a specific calculation method for the shear capacity of the WSCB is proposed, which includes the contributions from the steel web and concrete slab.